Measuring consumers' understanding of green marketing objective and concept in relation to environmental protection - Rosli, Norhizan; Abdullah, Kalthom; Haque, A. K. M. Ahasanul (American Scientific Publishers, 2018)
Green marketing has been an increasingly important element toward the practice of environmental protection. A term coined by marketing gurus, it is a structured topic, essentially offered in academic institutions. However, not every consumer enrols in such courses during their academic years. While some may gain their knowledge academically, others may acquire it through daily interactions with family members, friends, colleagues, business associations, or through the mass or social media. It is believed that the meaning and purpose of green marketing did not reach the general public, questioning the capability of green marketing in becoming a key factor in encouraging consumers to protect the environment. The lack of understanding the objective and concept of green marketing among consumers clearly reflect the unfavourable behaviour and support towards environmental protection. Due to this limitation, the intent of this study is to investigate the level of consumers’ understanding of green marketing objective and concepts through green marketing tools, as well as identify the common medium that contribute to their understanding. This study is also conducted to confirm the measurement items used to examine consumers’ understanding of green marketing particularly its objective and concepts, and tools. Self-constructed survey questionnaire was distributed to consumers, and analysed using a descriptive statistical and factor analysis. As expected, results indicated that consumers’ understanding about protecting the environment is not driven by green marketing objective and concept, but rather from daily interactions with their family members and within the society they are in.